Effect of processing parameters on the deposition of SiOx-like coatings on the surface of polypropylene films using glow discharge plasma assisted polymerization for tissue engineering applications. (September 2017) - Pandiyaraj, K. Navaneetha; Arun Kumar, A.; Ramkumar, M.C.; Kumar, S. Uday; Gopinath, P.; Cools, Pieter; De Geyter, N.; Morent, R.; Bah, M.; Shah, S. Ismat; Su, Pi-Guey; Deshmukh, R.R.
Abstract: In this investigation hexamethyldisiloxane (HMDSO) was used to deposit SiOx -like coatings on the surface of polypropylene (PP) films using an Ar + O2 glow discharge. Discharge potential and deposition time were varied systematically to optimize various SiOx coating properties such as hydrophilicity, oxidation state and surface homogeneity for possible tissue engineering applications. X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and contact angle were employed to analyze the said changes. Cell compatibility study of the SiOx films was done by in-vitro analysis, using NIH-3T3 (mouse embryonic fibroblast) cells to study the influence of the surface characteristics on cell adhesion and proliferation. The SiOx films were found to be highly hydrophilic, based on the contact angle and surface energy results. XPS confirmed the efficient incorporation of various oxidation states of Si and oxygen containing polar functional groups on the surface of PP film. Overall, a relatively smooth surface topography was observed, with distinct differences, depending on the applied plasma parameters. The in-vitro analysis characterized SiOx films as cyto-compatible, i.e improved non-toxicity, adhesion and proliferation of NIH-3T3 fibroblast cells. Overall, the developed films were found to exhibit a high potential for possible tissue engineering applications. Highlights: Developed SiOx like coating on the surface of PP films using glow discharge plasma assisted polymerization. Studied the influence of various operating parameters on the surface chemistry and morphology of the SiOx film. Mechanism of deposition of the SiOx films has been evidently examined. Various characterizations techniques were used to analysis the SiOx films. Examined cell compatibility and viability of SiOx films using in vitro studies.